THE CONCEPT OF STATE’S POLITICAL STABILITY IN THE PERSPECTIVE OF HADITH: Analysis of Government Hadiths in Sahih Muslim - Annisa Asyarofa; Teguh Dwi Cahyadi (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
The ideal state is characterized by how the state's political situation is. Stable state’s politic creates an ideal state for leaders, government, and the people. The state's political stability can be realized by the structure of the political system that regulates a state. The mindset of the people and governments, those who are strong in upholding and realizing the state's philosophical values which include the values of humanity, unity and social justice are steps for an effective political system that creates the state's political stability. The state’s political stability according to the perspective of hadith is theoritical review about the values of political stability contained in the hadiths of government. Sahih Muslim is one of the books written by Imam Muslim which discusses chapters containing hadiths about certain aspects. The purpose of this study is to analyze and find the concept of state’s political stability, hadiths about the state’s political stability in Sahih Muslim, and analysis of the concept of state’s political stability according to the hadith perspective. The approach in this research is a literature study by collecting data related to research from written sources and analyzing these data using deductive analysis methods. The results of the study indicate that: (1) The concept of state’s political stability is manifested by the adherence of the people and governments in realizing the state's philosophical values. (2) There are several redactions of hadiths about the state’s political stability in Sahih Muslim, among them are: The hadith from Abu Hurairah, the hadith from Ibn Umar, and the hadith from 'Auf bin Malik. (3) Analysis concept of state’s political stability according to the hadith perspective includes several discussions, among them are: state’s political stability according to the hadith perspective, interdependence of government hadiths in Sahih Muslim and state’s political stability, deviation of hadiths interpretation about state’s political stability in Sahih Muslim.